STRATEGI PENGEMBANGAN WISATA RELIGI DI ROKAN HULU TAHUN 2014 (SRTUDI: PENGELOLAAN MASJID AGUNG PASIR PENGARAIAN) - Vikry Al Ihsan; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Develop something that is indispensable to increase the attractiveness of tourists to visit .... Creating and creating the right places, of course, many aspects that must be attention and detail. There are 5 kinds of business Department of Culture and Tourism. Rokan Hulu in building religion, among others, technology, setting, leveling, and system settings.Results of projects transacted in Religious Park in Rokan Hulu. There are 5 kinds of business of Culture and Tourism Agency Rokan Hulu in developing relational such as technology, arrangement, arrangement, and system arrangement. Determine from existing development strategies several factors that can hamper tourism development that consists of human resources, and regulation.Keywords: Development, Religious Tourism